2006
DOI: 10.1007/s00114-006-0209-8
|View full text |Cite
|
Sign up to set email alerts
|

New evidence of shared dinosaur across Upper Jurassic Proto-North Atlantic: Stegosaurus from Portugal

Abstract: More than one century after its original description by Marsh in 1877, we report in this paper the first uncontroversial evidence of a member of the genus Stegosaurus out of North America. The specimen consists of a partial skeleton from the Upper Jurassic of Portugal, herein considered as Stegosaurus cf. ungulatus. The presence of this plated dinosaur in the upper Kimmeridgian-lower Tithonian Portuguese record and synchronic levels of the Morrison Formation of North America reinforces previous hypothesis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 26 publications
2
46
0
3
Order By: Relevance
“…The relationship of the Portuguese Late Jurassic sauropods to taxa from the North American Upper Jurassic Morrison Fm. (e.g., Lapparent and Zbyszewski, 1957) is currently believed to be less close than to other dinosaur groups (Galton, 1980;Pérez-Moreno et al, 1999;Mateus and Antunes, 2003;Escaso et al, 2007a;Malafaia et al, 2007Malafaia et al, , 2010aMalafaia et al, , 2010bHendrickx and Mateus, 2014;Malafaia et al, 2015) with no species or even genera reported on either side of the Atlantic. Recently, Tschopp et al (2015) have suggesed the presence of the genus Supersaurus in the Upper Jurassic of the Lusitanian Basin.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The relationship of the Portuguese Late Jurassic sauropods to taxa from the North American Upper Jurassic Morrison Fm. (e.g., Lapparent and Zbyszewski, 1957) is currently believed to be less close than to other dinosaur groups (Galton, 1980;Pérez-Moreno et al, 1999;Mateus and Antunes, 2003;Escaso et al, 2007a;Malafaia et al, 2007Malafaia et al, , 2010aMalafaia et al, , 2010bHendrickx and Mateus, 2014;Malafaia et al, 2015) with no species or even genera reported on either side of the Atlantic. Recently, Tschopp et al (2015) have suggesed the presence of the genus Supersaurus in the Upper Jurassic of the Lusitanian Basin.…”
Section: Introductionmentioning
confidence: 93%
“…The relatively abundant Portuguese vertebrate fossil record is important in understanding the relationships between North American and European fauna in this period. A combination of shared and exclusive taxa has been used as an argument to justify processes of dispersion and vicariance (Galton, 1980;Pérez-Moreno et al, 1999;Antunes and Mateus, 2003;Escaso et al, 2007a;Ortega et al, 2013). The relationship of the Portuguese Late Jurassic sauropods to taxa from the North American Upper Jurassic Morrison Fm.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case for example of the abundant and sometimes very well preserved, sphenodontian specimens whose relationship with members of the genus Opisthias described in North America and Europe is now in study (Ortega et al, 2006). Some recent tectonic and sedimentological analysis demonstrate the occurrence of a regional regressive phase during the uppermost Kimmeridgian -lowermost Tithonian related with the opening of the northern sector of the Atlantic Ocean (Kullberg, 2006;Escaso et al, 2007). This regional process, opposite to the global transgression noted on this time interval, have probably favoured the increase of emerge areas between the continental masses on both sides of the incipient north-Atlantic.…”
Section: Palaeobiogeographical Approachmentioning
confidence: 90%
“…Los estegosaurios alcanzaron una amplia distribución geográfica durante el Jurásico Superior, con registros conocidos en América del Norte, Asia, Europa y África Galton, 2012 (Galton, 1991;Casanovas-Cladellas et al, 1999;Escaso et al, 2007;Maidment et al, 2008). Dacentrurus también está presente en yacimientos clásicos de Inglaterra y Francia (Galton, , 1991 En los continentes gondwánicos, únicamente se ha documentado la presencia de tireóforos en el Jurásico Superior de África ( Fig.…”
Section: Jurásico Superiorunclassified